Essential statistics for public managers and policy analysts - Berman, Evan M.; Wang, XiaoHu 1962- (CQ Press, 2018)
Known for its brevity and student-friendly approach, Essential Statistics for Public Managers and Policy Analysts remains one of the most popular introductory books on statistics for public policy and public administration students, using carefully selected examples tailored specifically for them. The Fourth Edition continues to offer a conceptual understanding of statistics that can be applied readily to the real-life challenges of public administrators and policy analysts. The book provides examples from the areas of human resources management, organizational behavior, budgeting, and public policy to illustrate how public administrators interact with and analyze data. The text may be paired with the workbook Exercising Essential Statistics, Fourth Edition to help students apply each statistical technique introduced in the text.
Includes bibliographical references and index
Keywords: Public administration -- Statistical methods; Policy sciences -- Statistical methods